Tinjauan Peranan Income Audit Terhadap Pengendalian Internal Kas Pada Swiss-Belinn Hotel Bogor - Damayanti, Nur Alifiah; Andrianto, Toni; Rachman, Rachmawaty (Program Vokasi dan LPPM IBI Kesatuan, 2024)
The tourism industry currently plays an important role in improving the economy, especially for the Indonesian economy. It is proven that part of the tourism industry is experiencing rapid growth and development, which can help the development of other industries, including the hotel industry. Because the city of Bogor is not only a famous cultural city but also a famous tourist destination, the demand is high and the hotel accommodation sector is also growing. There are many different hotels in Bogor, from cheap hotels to four stars. The accommodation sector such as hotels is a promising business with high profits from the income earned. Some income must be managed so that everything runs smoothly, so that the adjustment of the income received is in the form of documentary evidence. Income audit is part of the finance and accounting department. The purpose of this final project is to determine the role of income audit on the internal control of Swiss-Belinn Hotel Bogor. The data analysis technique used includes descriptive analysis. By using descriptive data analysis techniques, the role and workflow of Income Audit are considered from start to finish. From the results of the analysis, it can be seen that the role of Income Audit in hotels including Swiss-Belinn Hotel Bogor is very important. The role of Income Audit Swiss-Belinn Hotel Bogor is running quite well and in accordance with existing procedures. Income Audit implements good control over the processing of business transaction income evidence assessment reports, especially for sales, so that the company's goal of generating income with a balance of evidence in the form of existing documents can be achieved in an effort to avoid data manipulation and income reduction. Keywords: Department of Finance and Accounting, Income Audit, income.